Regulation, targets and functions of CSK - Zhu, Shudong; Wang, Hui; Ranjan, Kamakshi; Zhang, Dianzheng (Frontiers in Cell and Developmental Biology, 2023)
Src family kinases (SFK) plays important roles in multiple signal transduction pathways. Aberrant activation of SFKs leads to diseases such as cancer, blood and bone pathologies. By phosphorylating and inactivating SFKs, the C-terminal Src kinase (CSK) serves as the key negative regulators of SFKs. Similar to Src, CSK is composed of SH3, SH2, and a catalytic kinase domain. However, the CSK kinase domain is intrinsically inactive while the Src kinase domain is intrinsically active. Multiple lines of evidence indicate that CSK is involved in various physiological processes including DNA repair, permeability of intestinal epithelial cells (IECs), synaptic activity, astrocyte-to-neuron communication, erythropoiesis, platelet homeostasis, mast cell activation, immune and inflammation responses, and dysregulation of CSK may lead to many diseases with different underlying molecular mechanisms. Recent findings also suggest that in addition to the well-established CSK-SFK axis, novel CSK-related pathways or targets as well as novel modes of CSK regulation exist. This review focuses on the recent progress in this field for an up-to-date understanding of CSK.